ANALISIS PENGARUH MOTIVASI DAN PENGAWASAN TERHADAP DISIPLIN KERJA KARYAWAN PT.TANIMAS EDIBLE OIL MEDAN - Sri Wiyenny; Imanuel Tarigan; Syawaluddin Syawaluddin (JURNAL BISNIS KOLEGA, 2019)
Abstract. PT.Tanimas Edible Oil  Medan is engaged in the sale of palm oil is having a problem employee motivation and supervision on employee disicipline is decreased in which can be seen from the lack og observance of working hours of employee who are often late.The purpose of research in this research is to determine the effect of motivation and supervision on Dicipline of work  PT. Tanimas Edible Oil Medan either partially or simultaneously. The method used in this research is quantitative descriptive rearsch type. Population in this research is all employees of PT. Tanimas Edible Oil Medan that totaling 41 people and samples used as many as 41 people. Data collection methods were conducted by interviews, questionnaires, documentation studies and review of the literature. Variables measured by Likert scale. Data analysis method used is multiple linear regression analysis.The results of this study indicate that simultaneously there are have influence of motivation and supervison on Employee Dicipline in PT. Tanimas Edible Oil Medan. And partially  supervision variable significantly influence to employee discipline of work PT. Tanimas Edible Oil Medan than communication variable. Keywords: Motivation, Supervision, Employee Dicipline